2015
DOI: 10.1038/bjc.2015.349
|View full text |Cite
|
Sign up to set email alerts
|

Urinary N1, N12-diacetylspermine is a non-invasive marker for the diagnosis and prognosis of non-small-cell lung cancer

Abstract: Background:Early detection of non-small-cell lung cancer (NSCLC) and accurate prognostic risk assessment could improve patient outcome. We examined the significance of urinary N1, N12-diacetylspermine (DiAcSpm) in the detection and prognostic stratification of NSCLC patients.Methods:A DiAcSpm/cutoff ratio (DASr) was established for 260 NSCLC patients, 99 benign lung disease patients, and 140 healthy volunteers, using colloidal gold aggregation methods. The DASr was compared between patients and healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 28 publications
1
34
1
Order By: Relevance
“…As a result, interest in the application of metabolomics to identify key metabolic differences related to pathological conditions has expanded. Indeed, metabolomics has been explored to gain insights into the pathophysiology of cancer, develop methods predictive of disease onset, and reveal new biomarkers relevant to disease diagnosis and prognosis [4][5][6] [ [10][11][12].…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, interest in the application of metabolomics to identify key metabolic differences related to pathological conditions has expanded. Indeed, metabolomics has been explored to gain insights into the pathophysiology of cancer, develop methods predictive of disease onset, and reveal new biomarkers relevant to disease diagnosis and prognosis [4][5][6] [ [10][11][12].…”
Section: Commentarymentioning
confidence: 99%
“…Takahashi et al found that urinary DAS was an prognostic marker for NSCLC (hazard ratio of 4.652 [95% CI, 2.092-10.35]), particularly in squamous cell carcinoma [10]. Additionally, urinary DAS and N1,N8-diacetylspermidine have shown promise as diagnostic markers for breast and colorectal cancers [14].…”
Section: Commentarymentioning
confidence: 99%
“…At present, the prognostic factors of lung cancer therapy are widely studied (9)(10)(11)(12). A prior study revealed that the DiAcSpm/cutoff ratio (DASr) is significantly increased in NSCLC, and the DASr was revealed to be an independent negative prognostic indicator in patients with NSCLC who underwent complete resection (13). The overexpression of SRY-box 2 may serve as a positive prognostic factor in patients with stage III squamous cell lung cancer receiving adjuvant radiotherapy (14).…”
Section: Introductionmentioning
confidence: 99%
“…Although their biochemistry and physiologic role is not well understood it was shown that they are implicated in growth and development of neoplastic cells [4][5][6]. Recently, their Nacetyl derivatives detected in urine were demonstrated to be of clinical use as markers of lung cancer [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, their Nacetyl derivatives detected in urine were demonstrated to be of clinical use as markers of lung cancer [7,8]. Thus, their elevated level may serve as non-specific tumor markers, especially for the pre-cancer diagnosis [4,[9][10][11][12][13]. Their level could be also used for the monitoring efficacy of therapy [9,10].…”
Section: Introductionmentioning
confidence: 99%